Biogenic amines in African locust bean (Parkia biglobosa) fermented seeds - (:unkn) unknown (My University, 2021)
African locust bean (Parkia biglobosa) is a legume widely spread in west Africa. The major consumed part is the seeds after processing in the so-called Soumbala in Ivory Coast. It is rich in proteins and lipids and used as a condiment to enhance sauce flavour. The seeds processing can be generalized as a first cooking to allow the dehulling of the seeds, a second cooking of the almond, an alkaline spontaneous fermentation of 2 to 3 days before final sun-drying. During fermentation, microorganisms belonging to the genus Bacillus are responsible of an extensive proteolysis (Odunfa et Adewuyi, 1985) and lipolysis (Ouoba et al. 2003). This gives the specific flavour to the product but may lead to toxic compounds such as biogenic amines. Biogenic amines accumulate by microbial decarboxylation of free amino acids and are thus susceptible to be present in fermented protein rich foods. They were reported in wine, cheese and fermented fish while they have not been studied yet in processed African locust bean seeds. The objective is to evaluate amino acids decarboxylation activities of Bacillus spp. isolates from Soumbala and biogenic amines content. Soumbala samples were collected among 6 producers in 3 regions of Ivory Coast. 52 Bacillus spp. strains were isolated and identified using API 50 CHB kits. Histidine, lysine, arginine, phenylalanine and ornithine decarboxylation activities and arginine dehydrogenase activities were determined in order to study their ability to produce histamine, cadaverine, phenylethylamine and putrescine. Soumbala samples were analysed for histamine, cadaverine, phenylethylamine and putrescine content. Bacillus spp. strains were identified as followed: B. subtilis (16); B. lentus (3), B. pumilus (1), Geobacillus stearothermophillus (5), B. megaterium (9), B. firmus (2), B. circulans (2), Brevibacillus non reactive (5), B. licheniformis (4), Aneurinibacillus aneuriniliticus (4), B. cereus (1). 16 strains did not show arginine deshyd
Keywords: African Research